Influence of Celebrity Endorsement on Brand Perception of Tecno Mobile - Dooshima, Ingbian Stephanie (Darul Yasin Al Sys, 2025)
As celebrity endorsement is now a common factor among advertisers and brands, this study focuses on the influence of celebrity endorsement on brand perception of Tecno Mobile. The study anchored on the principles of the Source Credibility Theory, Social Influence Theory and the Elaboration. Likelihood model. Using the survey design, questionnaire was employed to collect data from 400 Tecno mobile’s previous and current users residing in Abuja, Nigeria. Findings revealed that participants are exposed to celebrity endorsement very often in their daily life, its influence on their purchase decision depends on a number of factors, which includes the celebrity's credibility, the level of trust the consumer has in celebrities who endorse products or brands, and the type of product or brand being endorsed. The findings of this study revealed that majority of people preserve celebrity endorsements to be a good form of advertising because they believe celebrities are reliable. This study concludes that celebrity endorsement plays a major role in making purchase decisions, as well as the credibility of a celebrity. The study recommended that advertisers should define their target audience and the category of product while adopting celebrity endorsement.